(untitled) (Journal of Global Accounting, 2022)
Despite the changing economic environment and indicators locally and globally, prioritizing teachers welfare by way of better wage package towards attaining and sustaining robust productivity, academic excellence, quality service delivery, and competent skills development among students and pupils remain a lingering issue of debate and discourse among successive political administrations in Nigeria. To this end, the study intends to determine whether improved minimum wage package positively boosts teachers timely attendance to work. It further intends to examine the relationship between improved minimum wage package and teachers readiness to work overtime in school.. The study adopts the descriptive survey research design and further deploys the primary source of data through a 5-point Likert scale structured questionnaire. A sample of 200 Teachers in forty (40) selected Schools in Awka South Local Government Area of Anambra State, Nigeria were explored. Data responses and relevant hypotheses were analysed and tested using Pearson Correlation and the Multiple Regression statistical tools through the use of SPSS version 23. It was found out that improved minimum wage package will positively boost teachers’ timely attendance to work (f-critical 4.932 > f-table 2.42). It was also discovered that there is no statistical significant relationship between improved minimum wage package and Teachers readiness to work overtime in school (p-value 0.121 > 0.05). Based on these findings, the study concludes that the non-motivational attitude of the federal and state government to the plight of Teachers is believed to have negatively affected Teachers readiness to work overtime in schools where the need arises. The study therefore recommends that that there is need for Teachers to be assured that their monthly wage will be reviewed upward and higher by the government from time to time in order for them to minimize their attitude to running multiple jobs or taking up two or three teaching jobs which in most cases undermine their attendance and quality input to each job. It further recommends that government and owners of private schools should come up with a separate but reasonable compensation package(s) for settlement of substantial overtime work hours incurred by Teachers while discharging their duties.